Optimization of Guava Chewable Toothpaste Tablets - Md. Helmi, Nurhidayah; Mohd Hussin, Shuhaila; Hamzah, Muhammad Salahudin; Kamarul Nazli, Rabiatul Jannah; Tengku Muhamad Rozi, Tengku Nurul Husna; Mohamad Ashari, Zaidatul Shakila (2020)
The idea of this project is to innovate the guava chewable toothpaste tablets against oral bacteria. The guava fruit were processed to a fine powder. 3 different formulas were developed; tablet with charcoal, tablet without charcoal and tablet without humectant. Each tablet, total weight of 1 g, 13.25 ± 0.67 mm diameter and 6.20 ± 0.24 mm thickness, were formulated by incorporated the sea salt, stevia, sodium bicarbonate, sodium benzoate, glycerol and peppermint. Using disk diffusion method, the antibacterial sensitivity of the tablets was evaluated. The largest zone of inhibition was observed in formulated tablet with and without charcoal; 2.6 and 2.5 cm respectively, while 1.8 cm in tablet without humectant. Comparing to the positive control (commercialized toothpaste), the zone of inhibition observed was 3.2 ± 3 cm. The hardness and pH value of the tablets were also tested. The hardness was 0 (with charcoal), 0.13 (without charcoal) and 0.27 (without humectant) kN. The pH values of all tablets were in between 6 to 7.